PENGGUNAAN BAHASA INDONESIA DAN BAHASA GAUL DI KALANGAN MAHASISWA KAMPUS IBN LAMPUNG - Marselina Jupon, Rara (JECE (Journal of Ethics and Character Education), 2023)
Language is an important thing in human life. Through humans can be communicating. Besides language is used to convey an idea, ideas, opinions, feelings and thoughts to others. As well as a tool to develop themselves and socialize with others. A language must have a clear meaning so that when communication occurs there is no misunderstanding in its delivery. At present there are already several variations of language styles used in the community environment. The variation in language style is triggered by the development of communication technology that is developing very rapidly. The existence of this language development makes the style of language used by generations for different - different. Each generation will have the characteristics of each language style - each. The use of Indonesian that is good and right now has begun to be displaced by slang and feel accustomed to using slang.